(untitled) (Journal of Organizational Psychology, 2023)
Person-Organization (P-O) and Person-Job (P-J) fit are critical in retaining talent. Research has focused on the earliest time in an employee’s life with the company. The current research expanded this scope, to explore the role of fit perceptions and the HRM practices driving them, as moderated by employee tenure. The moderating effect of employee tenure on the relationships between HRM practices, fit perceptions, and retention related attitudes was examined. Results indicate tenure moderates the effects, such that for employees of very low or high tenure, P-O fit yields stronger predictive relationships with retention, whereas for employees of moderate tenure, P-J fit yields stronger predictive relationships.